Effect Of Fertilizer Treatment On Primary Metabolites Of Boerhaavia Diffusa Linn (Journal of Pharmaceutical Negative Results, 2023)
Metabolites are very important products for plants because they are directly involved in the all activity like reproduction, growth and their development and play a very significant role in their life.  They produced from metabolism and catalyzed by different types of enzymes. Estimation of primary metabolites have made in cutting of B. diffusa treated with different fertilizer doses as cow dung 10 ton/ha N:P:K 60:40:20 kg/ha, cow dung 10 ton/ha N:P-K 45:30:15 kg/ha, cow dung 10 ton/ha+ N:P:K 30:20:10 kg ha, and cow dung 5 ton/ha + N:P:K 60:40:20 kg/ha, cow dung 5 ton/ha+ NPK 45.30:15 kg/ha and cow dung 5 ton/ha+ N:P:K 30:20:10 kg/ha.Maximum amount of total sugar, was found with in treated cutting was found with root, leaf and stem respectively in cow dung 10 ton/ha + N:P:K 45:3±0:15 kg/ha.   Maximum amount of total soluble protein was found with root and stem respectively of cow dung 10 tan/ha+ N:P:K 45:30:15 kg/ha but in leaf it was maximum in cow dung 10 tanha N:P:K 30:20:10 kg/ha treated cutting and the maximum amount of total soluble protein was found with root and stem respectively of cow dung 10 tan/ha+ N:P:K 45:30:15 kg/ha but in leaf it was maximum in cow dung 10 tanha N:P:K 30:20:10 kg/ha treated cutting. Maximum amount of TCA precipitated protein was leaf in cow dung 10 ton/ha N:P:K 45:30:15 kg/ha treated cutting but in stem it was maximum in cow dung 10 ton/ha NPK 60:40:20 kg/ha treated cutting as compared to control.